Visualizing Elementary Students’ Conceptual Understanding in Science: A Pairplot Approach to Accuracy, Score, and Time - Ibrahim, Ibrahim (DIKODA JURNAL PENDIDIKAN SEKOLAH DASAR, 2025)
Elementary school students' understanding of science concepts is often evaluated only from the final score, without considering the cognitive process when answering questions. This study aims to visualize the relationship between scores, answer accuracy, and completion time through a pairplot approach. The method used is a descriptive quantitative study with data from 31 multiple-choice questions completed online via Quizizz. The results show a very strong positive correlation between the number of correct answers and the final score, and a strong negative correlation between incorrect answers and the score. Completion time shows a weak correlation to score and accuracy, indicating that speed is not the main determinant of success. Pairplots make it easier to identify student performance patterns, such as fast-accurate and slow-inaccurate groups. This visualization is useful in designing more targeted learning interventions. It is recommended that teachers integrate data visualization analysis into evaluations for a more comprehensive conceptual understanding.